2011
DOI: 10.1152/ajpcell.00377.2010
|View full text |Cite
|
Sign up to set email alerts
|

Akt directly regulates focal adhesion kinase through association and serine phosphorylation: implication for pressure-induced colon cancer metastasis

Abstract: Although focal adhesion kinase (FAK) is typically considered upstream of Akt, extracellular pressure stimulates cancer cell adhesion via Akt-dependent FAK activation. How Akt regulates FAK is unknown. We studied Akt-FAK interaction in colon cancer cells under 15 mmHg increased extracellular pressure. Pressure enhanced Akt-FAK association, blocked by inhibiting FAK or silencing Akt1 but not Akt2, and stimulated FAK serine phosphorylation in Caco-2 and human colon cancer cells from surgical specimens Akt1-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
69
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 57 publications
10
69
0
Order By: Relevance
“…This contrasts with the classical view of this pathway in which FAK is an upstream component of the pathway and largely insensitive to PI3K (7,8,10). However, recent reports have independently shown that serine/threonine phosphorylation of FAK by Akt, a major effector of PI3K, enhances its activation (53,54). Our results provide a plausible explanation for this apparent discrepancy in the literature because we showed that FAK becomes sensitized to PI3K-Akt regulation only when GIV enhances this pathway above a critical threshold.…”
Section: Discussionmentioning
confidence: 76%
“…This contrasts with the classical view of this pathway in which FAK is an upstream component of the pathway and largely insensitive to PI3K (7,8,10). However, recent reports have independently shown that serine/threonine phosphorylation of FAK by Akt, a major effector of PI3K, enhances its activation (53,54). Our results provide a plausible explanation for this apparent discrepancy in the literature because we showed that FAK becomes sensitized to PI3K-Akt regulation only when GIV enhances this pathway above a critical threshold.…”
Section: Discussionmentioning
confidence: 76%
“…Since it has been reported that PAK is localized at FAs (Stoletov et al, 2001;Brown et al, 2002;Chan et al, 2008;Delorme-Walker et al, 2011) and that PAK forms a complex with FAK (Stoletov et al, 2001), it is possible that PAK may also serve as a scaffold protein that facilitate the association between Akt1 and FAK at FAs, resulting in Akt1-mediated phosphorylation and activation of FAK in GF-stimulated cells. Since it has been shown in a recent study that Ser695 is necessary for pressure-induced activation of FAK in Caco-2 cells (Wang and Basson, 2011), it would also be worth examining whether the PAK-Akt1 pathway is also involved in pressure-induced activation of FAK in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…essential for pressure-induced activation of FAK in a recent study (Wang and Basson, 2011). We then investigated T700 (Fig.…”
Section: Akt1 Phosphorylates Fak At Ser695 and Thr700mentioning
confidence: 99%
“…Curiously, low-dose AKT inhibition increases ERK phosphorylation and increases the initial repopulation score, which is consistent with findings in other cell culture systems in which AKT activation impedes ERK phosphorylation (5). Furthermore, although AKT is generally thought of as downstream of FAK in the setting of ␤1-integrin activation (35), one recent report indicates that, in some settings, AKT might stimulate FAK activation (32). Because both ERK and AKT are known to regulate fibroblast proliferation in the setting of profibrotic stimuli (17,36), it is likely that inhibition of AKT at later time points would attenuate fibroblast survival and expansion or that addition of certain growth factors to the culture medium would lead to different results.…”
Section: L473mentioning
confidence: 99%